The Adoption of Technology Acceptance Model (TAM) and trust in influencing online purchase intention during the Covid-19 pandemic: Empirical evidence from Malaysia - Leong, Mei Kei *; Chaichi, Kamelia * (Human Resource Management Academic Research Society (www.hrmars.com), 2021)
Online purchasing has been embraced by customers due to its convenience and the raising issues of the Covid-19 pandemic. This research examines the factors influencing customers’ online purchase intention during the pandemic. Although a lot of research has been conducted regarding online purchasing, the factors influencing online purchase intention during the Covid-19 pandemic remain limited. Thus, this research incorporates the Theory of Acceptance Model and customer’s trust to determine the factors influencing customer purchase intention. The data were collected from 398 customers who purchased products through online platforms during the Covid-19 pandemic. The analysis of the results showed that various factors including “convenience”, “security”, “perceived ease of use”, “perceived usefulness”, and “trust” significantly influence customer online purchase intention during the Covid 19 pandemic. The findings of this study could provide practical implications to deploy effective online marketing strategies.